2020
DOI: 10.1021/acsnano.0c06610
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Atomic Catalysts Overcoming the Limitations of Single-Atom Catalysts

Abstract: Recent advances in heterogeneous single-atom catalysts (SACs), which have isolated metal atoms dispersed on a support, have enabled a more precise control of their surface metal atomic structure. SACs could reduce the amount of metals used for the surface reaction and have often shown distinct selectivity, which the corresponding nanoparticles would not have. However, SACs typically have the limitations of low-metal content, poor stability, oxidic electronic states, and an absence of ensemble sites. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 159 publications
0
93
0
Order By: Relevance
“…[12][13][14] However, the lack of ensemble sites prevents surface reactions that involve large molecules and some multi-step reactions. [15][16][17] Recent research demonstrated that "ensemble effects" between the metal single atoms and neighboring oxygen vacancies can favor the oxygen transfer and reactants adsorption, promoting the catalytic reaction efficiency with large molecules. [18][19][20] In our previous studies, we demonstrated the enhanced activity and selectivity of methanol dehydrogenation and n-hexane reforming when combining an oxygen vacancy with noble metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] However, the lack of ensemble sites prevents surface reactions that involve large molecules and some multi-step reactions. [15][16][17] Recent research demonstrated that "ensemble effects" between the metal single atoms and neighboring oxygen vacancies can favor the oxygen transfer and reactants adsorption, promoting the catalytic reaction efficiency with large molecules. [18][19][20] In our previous studies, we demonstrated the enhanced activity and selectivity of methanol dehydrogenation and n-hexane reforming when combining an oxygen vacancy with noble metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the mono‐atomic structure may face the significant challenge of the competitive adsorptions among reactants. [ 23 ] To overcome this challenge, multi‐atomic catalysts are highly desired. Recently, dual atomic catalysts (DAC) have been reported, where the introduction of the second metal atom enables the simultaneous adsorptions of different reactants, promotes the intermediate conversions, optimizes the binding strength, and supplies ensemble effects, improving the catalytic performances significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of this interaction will affect the interface charge transfer, the electronic structure of the metal, etc., which in turn affects the stability and catalytic performance of SACs. If the force is too weak, a single metal atom is prone to diffusion and agglomeration, and then sintering occurs, resulting in a decrease in the number of catalytic active centers and a decrease in catalytic activity; If the force is too strong, a single metal atom will be loaded on the carrier in a higher oxidation state [103], and its stability will be reduced, resulting in a significant decrease in activity or even loss of activity. In this review, we discuss the synthesis methods of SACs by atomic diffusion strategy based on the diffusion form of the precursor, and explain how individual atoms are carried on the carrier.…”
Section: Discussionmentioning
confidence: 99%